Factors influencing level of knowledge on noise pollution and it’s effects on physiological and psychological health of community in, Kuala Lumpur, 2006 - Mohd Aris, Mohd Shukri (Springer International Publishing AG, 2008)
A study to determine factors that influence the knowledge and sensitivity level to community noise pollution and its impacts to physiological and psychological health of community in Kuala Lumpur was carried out in December, 2005. Two communities were involved, 102 respondents from Community A (Flat Pekeliling, Jalan Tun Razak) and 87 respondents from Community B (Desa View Apartment, Melawati). The results in noise measurement showed that noise level parameters in Community A was higher than standard noise level parameters proposed by Department of Environment (DOE, Malaysia). The parameters were Leq, LIO and L9o according to standard time intervals by DOE. In Community B, no noise level parameters were exceeded standard noise levels by DOE. The results in survey interviews showed that the knowledge level and the sensitivity level in Community A were highly significant compared to Community B. The knowledge level analysis in both communities, non-parametric test showed that there were significant relationship (p<0.05) with marital status, work status and education level. The sensitivity level analysis, there were not showed any significant factors. The physiological health impact analysis in both communities, non-parametric test showed that cardiovascular symptoms and head ache were significantly correlated (p<0.05). In logistic regression, respiratory symptoms were significant correlation with factors of education level, age and year of stay. Whereas, cardiovascular symptoms were significant correlation with factors of education level and age. For head ache symptoms, it was significant correlation with age and community location. The psychological (sleep disturbance) health impacts analysis in both communities, non-parametric test showed that difficulties in falling asleep and time to fall asleep were significantly correlated (p<0.05). In logistic regression, difficulties in falling asleep were significant correlation with community location, whereas for time to fall asleep was significant correlation with factors of duration stay in house (hour and year), number of family members and community location. The psychological health impacts analysis in both communities, non-parametric test showed that stress, temper and loss of concentration were significantly correlated (p<0.05). In logistic regression, stress and temper symptoms were significant correlation with age and community location. For loss of concentration symptom, it was significant correlation with number of family members and community location. Conclusion, the higher level of knowledge and sensitivity level among community A are influenced by noise pollution impacts compared to community B. These comparisons were given the same influenced in terms of physiological and psychological health effects according to significant socio demographic factors involved.